2018
DOI: 10.1111/ced.13800
|View full text |Cite
|
Sign up to set email alerts
|

Novel and recurrent mutations in keratin 1 cause epidermolytic ichthyosis and palmoplantar keratoderma

Abstract: Novel and recurrent mutations in keratin 1 F. J. D. Smith et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…42,43 KRTs were prevailingly served as intracellular scaffolds, there is also considerable evidence reported that KRT1 exerts crucial functions in an inflammatory network as well as the maintenance of skin integrity in keratinocytes. 44 Here, we first detected that KRT1 was down-regulated in the small intestine after radiation exposure, while VA treatment increased the expression level of KRT1 at gene transcription and translation levels, suggesting that KRT1 may play a role in VA-induced amelioration of radiation injury. In support of this, we validated the hypothesis in vivo and in vitro to specifically down-regulated KRT1.…”
Section: Discussionmentioning
confidence: 77%
“…42,43 KRTs were prevailingly served as intracellular scaffolds, there is also considerable evidence reported that KRT1 exerts crucial functions in an inflammatory network as well as the maintenance of skin integrity in keratinocytes. 44 Here, we first detected that KRT1 was down-regulated in the small intestine after radiation exposure, while VA treatment increased the expression level of KRT1 at gene transcription and translation levels, suggesting that KRT1 may play a role in VA-induced amelioration of radiation injury. In support of this, we validated the hypothesis in vivo and in vitro to specifically down-regulated KRT1.…”
Section: Discussionmentioning
confidence: 77%
“…Dominant negative mutations of the genes that encode keratin 1 and 10 ( KRT1 , KRT10 ) cause epidermolytic ichthyosis (EI), previously also known as epidermolytic hyperkeratosis and bullous congenital ichthyosiform erythroderma of Brocq. Palmoplantar keratoderma (PPK) is usually associated with KRT1 mutations [ 1 ]. Mutations of genes that encode keratins, including KRT1 , are mostly missense mutations that affect the helix initiation (1A) and helix termination (2B) motifs, which are highly conserved regions of approximately 20 amino acids at the beginning and end of the central helical coiled-coil rod domain [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Keratin 1 (K1) -keratin 10 (K10) heterodimer is a hallmarker for keratinocyte differentiation [16]. K1 mutations are also associated with inherited skin diseases including epidermolytic ichthyosis, palmar-plantar keratoderma, and ichthyosis with confetti [6,13,14]. Several keratins, including K5, K7, K8/K18, K19, and K20, are of significance for immunohistochemical diagnosis of carcinomas [9].…”
Section: Introductionmentioning
confidence: 99%